Recreational anglers´ preferences and expenditures on live bait in Algarve - Araújo, Davide Morais (2021)
Marine recreational fishing has a great diversity of activities which can be linked to one another. Such is the case of shore-based angling and the use and harvest of live bait. The quantity and economic value referring to this activity is unsupervised in many parts of the world, especially in Europe, creating a “parallel economy” difficulting the assess of these characteristics. Most of these resources are marine polychaetes, but significant use and harvest of small crustaceans and sipunculids for their use in marine recreational fishing is observed globally. As several taxonomic groups are used all over the world, this study aimed to explore the preference, perceptions, quantities and expenditures of marine recreational rod shore-based anglers on live bait species, destined to increase the information needed to better understand the ecologic and socioeconomic impacts and help the development of management measures that can ensure the sustainability of harvesting activity. Interviews to rod shore-based anglers in main fishing location around the Algarve were conducted during summer months and was found that anglers preferred the use of both native and exotic live bait in their recreational fishing activity, mainly the Diopatra neapolitana, Perinereis sp., and Solen marginatus mostly obtained through local live bait shops. Extrapolation of direct expenses on live bait was estimated to be approximately 2.2 million €, of which comprised around 1.2 million € of native polychaete marine worms, 354000 € of the exotic Perinereis sp., 290000 € of S. marginatus, and 200000 € ghost shrimps (Upogebia sp.). The results of this study indicate that polychaete harvesting should be given equivalent attention to other fisheries, the need of research on the biology and densities of the most used polychaetes in Ria Formosa lagoon, efforts to provide updated information to recreational anglers and the continuous assessment of the live bait harvesting activity.